Evaluation of the effects of fulvestrant and micronized progesterone on the post-operative adhesion formation and ovarian reserve in rat model with immunohistochemical and biochemical analysis. (3rd August 2015) - Oner, Gokalp; Ulug, Pasa; Demirci, Elif; Kumtepe, Yakup; Gündogdu, Cemal
Abstract: Objective : To evaluate the effects of fulvestrant and micronized progesterone on post-operative adhesion formation and ovarian reserve in a rat uterine horn adhesion. Methods : In this prospective randomized controlled trial, 32 female Wistar albino rats were randomly divided into four groups including control group (Group 1), the control adhesion group (Group 2), 1 mg/kg daily intramuscular fulvestrant received group (Group 3) and 1 mg/kg daily oral micronized progesterone received group (Group 4). The extent and severity of adhesions were scored and samples were taken from adhesion areas to investigate the grades of adhesions according to the immunohistochemical scoring system. Ovarian reserves were measured with anti-Müllerian hormone (AMH) and histological ovarian follicles count. Results : The extent, severity and total adhesion scores were reduced in all treatment groups compared to control adhesion group (Group 2). Similarly, immunohistochemical adhesion scores were lower in the treatment groups. AMH and follicle count were significantly found lower in adhesion groups compared with control group. However, treatment groups were found to have higher ovarian reserve compared to control adhesion group (Group 2). Conclusions : Fulvestrant and micronized progesterone were found to reduce post-operative adhesion formations and have decreased detrimental effects of adhesion formation on ovarian reserve. Chinese abstract: 目的： 评价氟维司群和微粒化孕酮在大鼠宫角粘连中对术后粘连形成和卵巢储备的影响。 方法： 这项前瞻性随机对照试验将32只雌性Wistar大白鼠随机分为四组，包括对照组（1组），控制粘连组（2组），肌注1mg/（Kg·d）氟维司群组（3组）和口服1mg/（Kg·d）微粒化黄体酮组（4组）。根据免疫组化评分系统对粘连程度和严重程度进行评分，并从粘连区域取样以调查其粘连分级。通过抗苗勒管激素（AMH）和组织卵泡计数测定卵巢储备。结果： 相比于控制粘连组（2组），所有治疗组粘连程度、严重度以及总的粘连评分降低。同样，治疗组的免疫组化评分较低。粘连组的抗苗勒管激素和卵泡计数较对照组明显降低。然而，相比于控制粘连组，治疗组的卵巢储备较高。 结论： 氟维司群和微粒化孕酮可降低术后粘连的形成，减少粘连形成对卵巢储备的不利影响。